Mereformulasikan Area Pendekatan Sistematis dan Bijaksana dalam Pendidikan Islam untuk Anak di Sekolah Awal - Isma'il (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
The continuous development of problems in the field of education and religion demands the formulation of new paradigms, new theories, and new methods of operationalization that are able to solve new problems that are more complex, on the basis of which it is necessary to update thinking, study and research on Islamic education to reconstruct aspects of theological, philosophical, substantive, methodological, and learning systems in the hope that the implementation of religious education will be effective effectively. This paper is based on the aim of formulating an area of ??systematic and prudent approach in Islamic education for children in early school. From the results of the discussion concluded: 1) According to the Islamic view, education must prioritize faith education. History proves that education will produce education who lack moral character; 2) The historical reconstruction of Islamic philosophy as wisdom certainly indicates a thorough integration of modes of thinking and speaking which is the philosophy of philosophy into larger and speaking mode of thinking which is constitutive of historical Muslim society; 3) the critical area of ??Islamic education for children is the transmission of facts and information about Islam to the personality and character of Kaaffah, the curriculum must be relevant paradigm shift must be effective and relevant to the communities in which they live.